A flame retardant material containing bauxite and preparation method thereof

By introducing modified sepiolite and concave and concave and convex rod soil-nano silicon carbide composites into the flame retardant materials and optimizing the preparation process, the problems of complex preparation, high cost and deterioration of existing flame retardant materials are solved, and more efficient flame retardant performance and high temperature resistance are achieved.

CN118931326BActive Publication Date: 2025-03-11SHANXI MINGJING NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411237862.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-03-11
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The existing flame retardant materials are made in complex, costly and have limited flame retardant effects. Some materials have deteriorated performance during long-term use, affecting the fire retardant effect.

Method used

By introducing modified sepiolite and concave and concave and convex and concave-convex silicon carbide composites, combining the synergistic effects of multiple flame retardants, appropriate curing agents and dispersants are selected, and the preparation process is optimized to improve the flame retardant performance, high temperature resistance and adhesion ability of flame retardant materials.

Benefits of technology

The flame retardant performance, high temperature resistance and adhesion capabilities of bauxite flame retardant materials have been significantly improved, and the problems of complex processes, high costs and deterioration of traditional materials have been solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005028275440000181
    Figure BDA0005028275440000181
Patent Text Reader

Abstract

The present invention provides a flame retardant material containing bauxite and a preparation method thereof, and relates to the technical field of flame retardant materials. The flame retardant material containing bauxite of the present invention is prepared from the following raw materials in parts by weight: 25-30 parts of epoxy resin, 8-10 parts of modified sepiolite, 12-16 parts of bauxite, 12-16 parts of attapulgite-nano silicon carbide composite, 6-8 parts of curing agent, 0.5-1 parts of dispersant, 10-12 parts of hexaphenoxy cyclotriphosphazene, 6-10 parts of ammonium polyphosphate, 5-7 parts of starch, 3-5 parts of melamine, and 20-25 parts of water. The flame retardant material containing bauxite of the present invention improves the flame retardant performance, high temperature resistance and adhesion ability of the material by optimizing its composition and ratio, which is helpful to promote the technological progress and industrial upgrading of the fireproof material industry, and provides strong support for protecting the safety of life and property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant materials, and in particular to a flame retardant material containing bauxite and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry and construction, the requirements for fire resistance of materials are increasing day by day. As an important barrier to protect the safety of life and property, the research and development and application of flame retardant materials have become one of the hot topics in the field of materials science.

[0003] Bauxite, as a natural mineral resource with excellent fire resistance, high temperature resistance and chemical stability, shows great application potential in the field of flame retardant materials. Bauxite is mainly composed of aluminum oxide and silicate. Under high temperature environment, bauxite can remain stable and is not easy to melt or lose strength, which makes it an ideal raw material for preparing flame retardant materials. In addition, bauxite also has excellent insulation properties, chemical stability and certain mechanical strength, which together give it unique advantages as a flame retardant material.

[0004] In the field of fire prevention, bauxite can be added as a flame retardant to various fireproof materials, such as fireproof coatings, flame-retardant plastics, etc. Its high temperature stability and chemical stability can effectively isolate the fire source and inhibit the spread of fire, thereby improving the overall fireproof performance of the material. At the same time, bauxite also has good thermal insulation and thermal stability, and can be used as a flame retarder to slow down the spread of flames and buy precious time for personnel evacuation and fire extinguishing.

[0005] Although bauxite has broad application prospects in flame retardant materials, there are still some shortcomings in the prior art. For example, the preparation methods of traditional flame retardant materials often have problems such as complex processes, high costs, and limited flame retardant effects. In addition, some flame retardant materials may experience performance degradation during long-term use, affecting the fireproof effect. Therefore, it is of great significance to develop a flame retardant material containing bauxite with excellent performance, simple preparation, and controllable cost. Based on this, the present invention provides a flame retardant material containing bauxite and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a flame retardant material containing bauxite and a preparation method thereof, which optimizes the flame retardant properties of the flame retardant material and also improves the high temperature resistance and adhesion ability of the material.

[0007] On the one hand, the present invention provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 25-30 parts of epoxy resin, 8-10 parts of modified sepiolite, 12-16 parts of bauxite, 12-16 parts of attapulgite-nano silicon carbide composite, 6-8 parts of curing agent, 0.5-1 part of dispersant, 10-12 parts of hexaphenoxy cyclotriphosphazene, 6-10 parts of ammonium polyphosphate, 5-7 parts of starch, 3-5 parts of melamine, and 20-25 parts of water.

[0008] Furthermore, the preparation method of the modified sepiolite includes: mixing and stirring sepiolite and H2O2 solution, carrying out a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 110-120°C, and the reaction time is 18-20h. After the reaction is completed, the material A is cooled and centrifugally dried to obtain material A, material A is added to toluene and mixed, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added when the temperature is heated to 60-70°C, and the reaction is refluxed with stirring for 10-12h. The precipitate is collected after filtration and washed with ethanol for 3-5 times to obtain the modified sepiolite.

[0009] Furthermore, the mass concentration of H2O2 is 20-24%.

[0010] Furthermore, the usage ratio of the sepiolite and the H2O2 solution is (1-2) g:10 mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is (1-2) g:(90-100) mL:(0.5-1) g.

[0011] Furthermore, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.15-0.2 mol / L dilute hydrochloric acid for 30-40 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it into ethanol together with nano silicon carbide, adding a coupling agent, and stirring it at 500-600r / min for 1.5-2.5h.

[0012] Furthermore, the weight ratio of the pretreated attapulgite, nano-silicon carbide, ethanol, and coupling agent is (4-5): (2-3): (50-60): (1.5-2).

[0013] Furthermore, the coupling agent comprises isopropyl distearoyloxyaluminate and γ-methacryloxypropyltrimethoxysilane in a weight ratio of 1:(1.2-1.4).

[0014] Furthermore, the curing agent is diethylenetriamine, and the dispersant includes at least one of BYK-307, BYK-330, and BYK-341.

[0015] On the other hand, the present invention also provides a method for preparing a flame retardant material containing bauxite, the steps comprising: stirring modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water at 550-650 r / min for 35-45 min, then adding epoxy resin and curing agent and continuing stirring for 50-60 min to obtain the flame retardant material.

[0016] The beneficial effects of the present invention are:

[0017] The present invention significantly improves the flame retardant properties, high temperature resistance and adhesion ability of the bauxite-containing flame retardant material through the introduction of modified sepiolite and attapulgite-nano silicon carbide composites, the synergistic effect of multiple flame retardants, the selection of curing agents and dispersants, and the optimization of the preparation process.

[0018] In the present invention, modified sepiolite is selected as a raw material. First, in the preparation method of modified sepiolite, through the oxidation of hydrogen peroxide (H2O2), some functional groups on the surface of sepiolite may undergo oxidation reaction, introducing more oxygen-containing groups, such as hydroxyl (-OH) and the like. These oxygen-containing groups not only increase the hydrophilicity of sepiolite, but also provide more reaction sites for subsequent silane coupling agent modification. The addition of silane coupling agent (such as γ-(2,3-epoxypropoxy)propyltrimethoxysilane) reacts with the hydroxyl on the surface of sepiolite through its epoxy group to form a stable chemical bond, thereby achieving organic modification of sepiolite. This modification not only optimizes the flame retardant properties of the flame retardant material, but also improves the high temperature resistance and adhesion of the material through the introduction of chemical bonds. In addition, the raw materials of the flame retardant material of the present invention also include bauxite, which, as an inorganic mineral material, has excellent properties such as high temperature resistance, corrosion resistance and mechanical strength. When modified sepiolite is compounded with bauxite, the two can complement each other's advantages and further improve the comprehensive performance of the composite material.

[0019] When the attapulgite-nano silicon carbide composite is selected as the raw material in the present invention, the attapulgite is first pretreated, and then a complex coupling agent is added. The coupling agent forms chemical bonds or strong interactions with the attapulgite and nano silicon carbide surfaces respectively through the reactive groups at both ends thereof, thereby enhancing the bonding force between the two. Among them, nano silicon carbide has excellent high temperature resistance and antioxidant properties, and can form a protective layer at high temperatures to prevent the spread of flames and the penetration of oxygen. After being compounded with attapulgite, the two act synergistically to further improve the flame retardant properties of the composite material. When combined with bauxite, an aluminum oxide protective layer can be formed at high temperatures, and a dense protective layer can be formed when heated to isolate oxygen and heat, and together constitute multiple flame retardant barriers, thereby delaying combustion, and forming a synergistic effect with the aluminum oxide in the attapulgite-nano aluminum oxide composite to enhance the flame retardant effect.

[0020] In the present invention, an aluminate coupling agent and a silane coupling agent are used in combination to prepare a attapulgite-nano silicon carbide composite. Both the aluminate coupling agent and the silane coupling agent can form chemical bonds or strong interactions with the surfaces of attapulgite and nano silicon carbide. When used in combination, they can act together on the interface of the composite to form a more solid bonding layer, reduce interface defects, and improve the overall structural stability of the composite. This enhanced interfacial bonding force helps to maintain the integrity of the composite during the combustion process and prevent the internal materials from being exposed to the flame too early. Aluminate coupling agents and silane coupling agents may produce different flame retardant mechanisms during the combustion process. For example, silane coupling agents may form a silicon dioxide protective layer at high temperatures, while aluminate coupling agents may promote the generation of flame retardant products such as aluminum oxide. When used in combination, the two coupling agents can work synergistically to jointly promote the generation and distribution of flame retardant products to form a more effective flame retardant barrier. In addition, they can act together on the molecular chain of the composite to increase the interaction force between molecules and increase the thermal decomposition temperature of the composite. This helps to slow down the thermal decomposition of the composite during combustion, reduce the release of combustible gases, and thus improve flame retardant properties. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the raw materials can be obtained commercially. Among them, the epoxy resin is epoxy resin E-12.

[0022] Example 1

[0023] The present embodiment provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of modified sepiolite, 14 parts of bauxite, 14 parts of attapulgite-nano silicon carbide composite, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0024] The preparation method of the modified sepiolite comprises: mixing and stirring sepiolite and a H2O2 solution with a mass concentration of 22%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 115°C and the reaction time is 18-20 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 65°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 11 hours, collecting the precipitate after filtering, and washing it with ethanol for 4 times to obtain the modified sepiolite;

[0025] Among them, the usage ratio of the sepiolite and H2O2 solution is 1.5g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.5g:95mL:0.75g.

[0026] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.17 mol / L dilute hydrochloric acid for 35 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it to ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 550r / min for 2 hours.

[0027] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 4.5:2.5:55:1.7.

[0028] The coupling agent comprises isopropyl distearoyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.3.

[0029] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0030] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0031] Modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the obtained product.

[0032] Example 2

[0033] The present embodiment provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 25 parts of epoxy resin, 8 parts of modified sepiolite, 12 parts of bauxite, 12 parts of attapulgite-nano silicon carbide composite, 6 parts of curing agent, 0.5 parts of dispersant, 10 parts of hexaphenoxy cyclotriphosphazene, 6 parts of ammonium polyphosphate, 5 parts of starch, 3 parts of melamine, and 20 parts of water;

[0034] The preparation method of the modified sepiolite comprises: mixing sepiolite and a H2O2 solution with a mass concentration of 20%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 110°C and the reaction time is 18 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 60°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 10 hours, collecting the precipitate after filtering, and washing with ethanol for 3-5 times to obtain the modified sepiolite;

[0035] Among them, the usage ratio of the sepiolite and the H2O2 solution is 1g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1g:90mL:0.5g.

[0036] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.15 mol / L dilute hydrochloric acid for 30 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it into ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 500r / min for 1.5 hours.

[0037] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 4:2:50:1.5.

[0038] The coupling agent comprises isopropyl distearyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.2.

[0039] The curing agent is diethylenetriamine, and the dispersing agent is BYK-330.

[0040] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0041] The modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 550 r / min for 35 minutes, then epoxy resin and curing agent are added and stirring is continued for 50 minutes to obtain the product.

[0042] Example 3

[0043] The present embodiment provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 30 parts of epoxy resin, 10 parts of modified sepiolite, 16 parts of bauxite, 16 parts of attapulgite-nano silicon carbide composite, 8 parts of curing agent, 1 part of dispersant, 12 parts of hexaphenoxy cyclotriphosphazene, 10 parts of ammonium polyphosphate, 7 parts of starch, 5 parts of melamine, and 25 parts of water;

[0044] The preparation method of the modified sepiolite comprises: mixing sepiolite and a H2O2 solution with a mass concentration of 24%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 120°C and the reaction time is 20 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 70°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 12 hours, filtering and collecting the precipitate, and washing with ethanol 5 times to obtain the modified sepiolite;

[0045] Among them, the usage ratio of the sepiolite and the H2O2 solution is 2g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 2g:100mL:1g.

[0046] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.2 mol / L dilute hydrochloric acid for 40 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it into ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 600r / min for 2.5 hours.

[0047] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 5:3:60:2.

[0048] The coupling agent comprises isopropyl distearyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.4.

[0049] The curing agent is diethylenetriamine, and the dispersing agent is BYK-341.

[0050] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0051] The modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 650 r / min for 45 minutes, then epoxy resin and curing agent are added and stirring is continued for 60 minutes to obtain the product.

[0052] Example 4

[0053] The present embodiment provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 25 parts of epoxy resin, 10 parts of modified sepiolite, 12 parts of bauxite, 16 parts of attapulgite-nano silicon carbide composite, 6 parts of curing agent, 1 part of dispersant, 10 parts of hexaphenoxy cyclotriphosphazene, 10 parts of ammonium polyphosphate, 5 parts of starch, 5 parts of melamine, and 20 parts of water;

[0054] The preparation method of the modified sepiolite comprises: mixing sepiolite and a H2O2 solution with a mass concentration of 20%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 120°C and the reaction time is 18 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 70°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 10 hours, collecting the precipitate after filtering, and washing it with ethanol 5 times to obtain the modified sepiolite;

[0055] Among them, the usage ratio of the sepiolite and the H2O2 solution is 1g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 2g:90mL:1g.

[0056] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.15 mol / L dilute hydrochloric acid for 40 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it into ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 500r / min for 2.5 hours.

[0057] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 4:3:50:2.

[0058] The coupling agent comprises isopropyl distearyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.2.

[0059] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0060] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0061] The modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 650 r / min for 35 minutes, then epoxy resin and curing agent are added and stirring is continued for 60 minutes to obtain the product.

[0062] Comparative Example 1

[0063] The present comparative example provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of modified sepiolite, 14 parts of bauxite, 14 parts of attapulgite-nano silicon carbide composite, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0064] The preparation method of the modified sepiolite includes: mixing and stirring sepiolite and a H2O2 solution with a mass concentration of 22%, and performing a hydrothermal reaction in a reactor. The temperature of the hydrothermal reaction is 115°C, and the reaction time is 18-20 hours. After the reaction is completed, the modified sepiolite is cooled and centrifugally dried to obtain the modified sepiolite. The usage ratio of the sepiolite and the H2O2 solution is 1.5g:10mL.

[0065] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.17 mol / L dilute hydrochloric acid for 35 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it to ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 550r / min for 2 hours.

[0066] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 4.5:2.5:55:1.7.

[0067] The coupling agent comprises isopropyl distearoyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.3.

[0068] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0069] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0070] Modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the obtained product.

[0071] Comparative Example 2

[0072] The present comparative example provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of modified sepiolite, 14 parts of bauxite, 14 parts of attapulgite-nano silicon carbide composite, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0073] The preparation method of the modified sepiolite comprises: adding sepiolite to toluene and mixing, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane when heating to 65°C, stirring and refluxing for 11 hours, collecting the precipitate after filtering, and washing it with ethanol for 4 times to obtain the modified sepiolite; wherein the amount ratio of the sepiolite, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.5g:95mL:0.75g.

[0074] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.17 mol / L dilute hydrochloric acid for 35 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it to ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 550r / min for 2 hours.

[0075] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 4.5:2.5:55:1.7.

[0076] The coupling agent comprises isopropyl distearoyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.3.

[0077] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0078] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0079] Modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the obtained product.

[0080] Comparative Example 3

[0081] The present comparative example provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of sepiolite, 14 parts of bauxite, 14 parts of attapulgite-nano silicon carbide composite, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0082] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.17 mol / L dilute hydrochloric acid for 35 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it to ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 550r / min for 2 hours.

[0083] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 4.5:2.5:55:1.7.

[0084] The coupling agent comprises isopropyl distearoyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.3.

[0085] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0086] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0087] Sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the product.

[0088] Comparative Example 4

[0089] The present comparative example provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of modified sepiolite, 14 parts of bauxite, 9 parts of attapulgite, 5 parts of nano silicon carbide, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0090] The preparation method of the modified sepiolite comprises: mixing and stirring sepiolite and a H2O2 solution with a mass concentration of 22%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 115°C and the reaction time is 18-20 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 65°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 11 hours, collecting the precipitate after filtering, and washing it with ethanol for 4 times to obtain the modified sepiolite;

[0091] Among them, the usage ratio of the sepiolite and H2O2 solution is 1.5g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.5g:95mL:0.75g.

[0092] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0093] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0094] The modified sepiolite, bauxite, attapulgite, nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the product.

[0095] Comparative Examples

[0096] The present comparative example provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of modified sepiolite, 14 parts of bauxite, 14 parts of attapulgite-nano silicon carbide composite, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0097] The preparation method of the modified sepiolite comprises: mixing and stirring sepiolite and a H2O2 solution with a mass concentration of 22%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 115°C and the reaction time is 18-20 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 65°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 11 hours, collecting the precipitate after filtering, and washing it with ethanol for 4 times to obtain the modified sepiolite;

[0098] Among them, the usage ratio of the sepiolite and H2O2 solution is 1.5g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.5g:95mL:0.75g.

[0099] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.17 mol / L dilute hydrochloric acid for 35 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it to ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 550r / min for 2 hours.

[0100] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 4.5:2.5:55:1.7.

[0101] The coupling agent is γ-methacryloxypropyltrimethoxysilane.

[0102] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0103] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0104] Modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the obtained product.

[0105] Comparative Example 6

[0106] The present comparative example provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of modified sepiolite, 14 parts of bauxite, 14 parts of modified nano silicon carbide, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0107] The preparation method of the modified sepiolite comprises: mixing and stirring sepiolite and a H2O2 solution with a mass concentration of 22%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 115°C and the reaction time is 18-20 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 65°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 11 hours, collecting the precipitate after filtering, and washing it with ethanol for 4 times to obtain the modified sepiolite;

[0108] Among them, the usage ratio of the sepiolite and H2O2 solution is 1.5g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.5g:95mL:0.75g.

[0109] The preparation method of the modified nano-silicon carbide comprises: adding nano-silicon carbide to ethanol, adding a coupling agent, and stirring at 550 r / min for 2 hours. The weight ratio of the nano-silicon carbide, ethanol, and coupling agent is 2.5:55:1.7.

[0110] The coupling agent comprises isopropyl distearoyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.3.

[0111] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0112] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0113] The modified sepiolite, bauxite, modified nano silicon carbide, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the product.

[0114] Comparative Example 7

[0115] The present comparative example provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of modified sepiolite, 14 parts of bauxite, 14 parts of modified attapulgite, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0116] The preparation method of the modified sepiolite comprises: mixing and stirring sepiolite and a H2O2 solution with a mass concentration of 22%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 115°C and the reaction time is 18-20 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 65°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 11 hours, collecting the precipitate after filtering, and washing it with ethanol for 4 times to obtain the modified sepiolite;

[0117] Among them, the usage ratio of the sepiolite and H2O2 solution is 1.5g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.5g:95mL:0.75g.

[0118] The preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.17 mol / L dilute hydrochloric acid for 35 minutes, drying it and crushing it to obtain pretreated attapulgite, then adding it to ethanol, adding a coupling agent and stirring it at 550r / min for 2 hours.

[0119] Wherein, the weight ratio of the pretreated attapulgite, ethanol and coupling agent is 4.5:55:1.7.

[0120] The coupling agent comprises isopropyl distearoyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.3.

[0121] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0122] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0123] Modified sepiolite, bauxite, modified attapulgite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the product.

[0124] Comparative Example 8

[0125] The comparative example provides a flame retardant material containing bauxite, which is prepared from the following raw materials in parts by weight: 27 parts of epoxy resin, 9 parts of modified sepiolite, 14 parts of attapulgite-nano silicon carbide composite, 7 parts of curing agent, 0.7 parts of dispersant, 11 parts of hexaphenoxy cyclotriphosphazene, 8 parts of ammonium polyphosphate, 6 parts of starch, 4 parts of melamine, and 22 parts of water;

[0126] The preparation method of the modified sepiolite comprises: mixing and stirring sepiolite and a H2O2 solution with a mass concentration of 22%, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 115°C and the reaction time is 18-20 hours, cooling after the reaction is completed, and centrifugally drying to obtain material A, adding material A to toluene, heating to 65°C, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and refluxing for 11 hours, collecting the precipitate after filtering, and washing it with ethanol for 4 times to obtain the modified sepiolite;

[0127] Among them, the usage ratio of the sepiolite and H2O2 solution is 1.5g:10mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.5g:95mL:0.75g.

[0128] Among them, the preparation method of the attapulgite-nano silicon carbide composite includes: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.17 mol / L dilute hydrochloric acid for 35 minutes, drying and crushing it to obtain pretreated attapulgite, then adding it to ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 550r / min for 2 hours.

[0129] Wherein, the weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is 4.5:2.5:55:1.7.

[0130] The coupling agent comprises isopropyl distearoyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:1.3.

[0131] The curing agent is diethylenetriamine, and the dispersant is BYK-307.

[0132] The method for preparing the flame retardant material containing bauxite in this embodiment comprises the following steps:

[0133] The modified sepiolite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 600 r / min for 40 minutes, then epoxy resin and curing agent are added and stirring is continued for 55 minutes to obtain the obtained product.

[0134] Test Example: The flame retardant materials prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-8 were subjected to the following tests:

[0135] High temperature (heat resistance) insulation performance test: Apply the coating to a 90mm×90mm×2mm steel test piece with a coating thickness of 1.1-1.2mm. Place the steel test piece in a hydrocarbon flame for burning. While ensuring that the coating surface temperature is 1000°C, record the experimental time and the corresponding substrate temperature, and observe the coating status at the same time.

[0136] Flame retardancy test: The test method and standard refer to UL94 flame retardancy test;

[0137] Fire resistance test: The fire resistance limit (min) of the coating at 220°C is tested in accordance with the national standard GB / T15442.2;

[0138] Adhesion test: Refer to the national standard GN / T1720-89 for coating adhesion test.

[0139] The results are shown in Table 1 below:

[0140] Table 1

[0141]

[0142] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A flame retardant material containing bauxite, characterized in that: The invention is prepared from the following raw materials in parts by weight: 25-30 parts of epoxy resin, 8-10 parts of modified sepiolite, 12-16 parts of bauxite, 12-16 parts of attapulgite-nano silicon carbide composite, 6-8 parts of curing agent, 0.5-1 part of dispersant, 10-12 parts of hexaphenoxy cyclotriphosphazene, 6-10 parts of ammonium polyphosphate, 5-7 parts of starch, 3-5 parts of melamine and 20-25 parts of water; The preparation method of the modified sepiolite comprises: mixing and stirring sepiolite and H2O2 solution, performing a hydrothermal reaction in a reactor, wherein the temperature of the hydrothermal reaction is 110-120°C, and the reaction time is 18-20 hours. After the reaction is completed, cooling and centrifugal drying are performed to obtain material A, material A is added to toluene and mixed, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added when the temperature is heated to 60-70°C, and reflux reaction is performed with stirring for 10-12 hours, and precipitates are collected after filtering, and washed with ethanol for 3-5 times to obtain the modified sepiolite. The usage ratio of the sepiolite and H2O2 solution is (1-2) g:10 mL; the usage ratio of the material A, toluene and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane is (1-2) g:(90-100) mL:(0.5-1) g; The preparation method of the attapulgite-nano silicon carbide composite comprises: sieving the attapulgite to remove impurities, washing it with distilled water several times to remove surface attachments, then soaking it in 0.15-0.2 mol / L dilute hydrochloric acid for 30-40 min, drying it and crushing it to obtain pretreated attapulgite, then adding it to ethanol together with nano silicon carbide, adding a coupling agent and stirring it at 500-600 r / min for 1.5-2.5 h; The weight ratio of the pretreated attapulgite, nano silicon carbide, ethanol and coupling agent is (4-5): (2-3): (50-60): (1.5-2).

2. The flame retardant material containing bauxite according to claim 1, characterized in that: The particle size of the sepiolite is 200-300 meshes.

3. The flame retardant material containing bauxite according to claim 1, characterized in that: The mass concentration of the H2O2 is 20-24%.

4. The flame retardant material containing bauxite according to claim 1, characterized in that: The coupling agent comprises isopropyl distearoyloxyaluminate and gamma-methacryloxypropyltrimethoxysilane in a weight ratio of 1:(1.2-1.4).

5. The flame retardant material containing bauxite according to claim 1, characterized in that: The curing agent is diethylenetriamine, and the dispersant includes at least one of BYK-307, BYK-330, and BYK-341.

6. A method for preparing a flame retardant material containing bauxite according to any one of claims 1 to 5, characterized in that the steps include: The modified sepiolite, bauxite, attapulgite-nano silicon carbide composite, dispersant, hexaphenoxy cyclotriphosphazene, ammonium polyphosphate, starch, melamine and water are stirred at 550-650 r / min for 35-45 minutes, then epoxy resin and curing agent are added and stirring is continued for 50-60 minutes to obtain the product.

Citation Information

Patent Citations

  • Sepiolite nano flame-retardant fiber as well as preparation method thereof and flame-retardant composite material using same for strengthening and toughening

    CN101913782A

  • Light cement foam insulation plate and production method thereof

    CN103183521A